กระบวนการสร้างเสริมการบริหารจัดการ ธนาคารข้าว และการลดต้นทุนในการผลิตข้าว กรณีศึกษา: บ้านหินปูน ตำบลเขวาใหญ่ อำเภอกันทรวิชัย จังหวัดมหาสารคาม - อรรถรังสรรค์ นวลละออง (Area Based Development Research Journal, 2015)
บทคัดย่อไม่สมบูรณ์ Supporting management process of rice bank and cost cutback in rice production: Case Study of Banhinpoon, Khaowyai Sub-district, Kantarawichai District, Maha Sarakham Province This research was a Participatory Action Research that aimed 1) to study the context of community, problematic situation and the effect on Banhinpoon community, 2) to study the background and managing system of rice bank of Banhinpoon community and 3) to study the appropriate cost cutback process of rice production of Banhinpoon community. The research methodology was divided into 3 phase. The first phase was a preparation; reinforce the effectiveness of research team and data collection. The second phase was action-taking. The third phase was the conclusion and evaluation of the project. Research tools were interview and colloquy with village headman, assistant village headman, member of sub-district administration organization, academician, student and villagers. The area of the study was Banhinpoon, Khaowyai Sub-district, Kantarawichai District, Maha Sarakham Province. The research result showed that community villagers can initiate and promote their thinking process after getting the suggestion from the research team and lecturer. The participation of villagers have changed quantitatively and qualitatively that almost 70% of the villagers participated in the project and dared to share idea in group discussion. The committee of the rice bank and villagers have cooperated in solving the rice bank problems. For example, when the member returned the low quality rice that is not suitable for using as seed, the rice bank committee sold them and used the money for buying qualified seed for loan. Trail planting farm is done for getting high quality seeds that will be brought back to the rice bank for loan. Other activities done under the project such as, learning how to do bookkeeping, managing capital, making biofertilizer and properly growing rice could reduce cost and add more income. Consequently, villagers gain better living condition, become self-dependent and live with sustainability.